5
$\begingroup$

The question is to find $x\in\left(0,\frac{\pi}{2}\right)$:

$$\frac {\sqrt3 - 1}{\sin x} + \frac {\sqrt3 + 1}{\cos x} = 4\sqrt2 $$

What I did was to take the $\cos x$ fraction to the right and try to simplify ;

But it looked very messy and trying to write $\sin x$ in terms of $\cos x$ didn't help.

Is there a more simple (elegant) way to do this.

$\endgroup$
  • 3
    $\begingroup$ divide both sides by $2\sqrt{2}$ and use the fact that $\sin(\frac{\pi}{6}) = \frac{\sqrt{3}-1}{2\sqrt{2}}$ and $\cos(\frac{\pi}{6}) = \frac{\sqrt{3}+1}{2\sqrt{2}}$ $\endgroup$ – dezdichado Mar 20 '16 at 8:56
  • 5
    $\begingroup$ $\sin \frac \pi6$ is $\frac 12$, did you mean $\frac \pi{12}$? $\endgroup$ – user26977 Mar 20 '16 at 8:59
10
$\begingroup$

$\sin(\frac{\pi}{12}) = \frac{\sqrt{3}-1}{2\sqrt{2}}$ and $\cos(\frac{\pi}{12}) = \frac{\sqrt{3}+1}{2\sqrt{2}}$. Plugging them into your equation yields $\sin(x+\frac{\pi}{12}) = \sin(2x)$. So $x = \frac{\pi}{12}$

$\endgroup$
  • $\begingroup$ It $\pi/12$ not $\pi/6$ $\endgroup$ – lab bhattacharjee Mar 20 '16 at 9:00
  • $\begingroup$ yes edited accordingly $\endgroup$ – dezdichado Mar 20 '16 at 9:01
7
$\begingroup$

Another approach is to write the equation as

$(\sqrt{3} - 1) \cos x +(\sqrt{3} + 1) \sin x = 4 \sqrt2 \sin x \cos x$

then rearranging gives

$\frac{\sqrt{3} - 1}{2 \sqrt{2}} \cos x +\frac{\sqrt{3} + 1}{2 \sqrt{2}} \sin x = 2 \sin x \cos x$.

Now note that $(\frac{\sqrt{3} - 1}{2 \sqrt{2}})^2 +(\frac{\sqrt{3} + 1}{2 \sqrt{2}})^2 = \frac{1}{8} ((3 -2 \sqrt{3} + 1) + (3 +2 \sqrt{3} + 1) = 1$ so that we can write $\frac{\sqrt{3} - 1}{2 \sqrt{2}}$ as the $\sin$ of some angle, say $\alpha$, and identify $\frac{\sqrt{3} + 1}{2 \sqrt{2}}$ as $\cos \alpha$.

Then you have to solve $\sin(\alpha + x) = \sin(2x)$, with $\tan \alpha = \frac{\sqrt{3} - 1}{\sqrt{3} + 1}$.

$\endgroup$
5
$\begingroup$

Replace $\sqrt3=\tan60^\circ,1=\tan45^\circ$

to find $$\sin(15^\circ+x)=2\sin x\cos x=\sin2x$$

Now if $\sin y=\sin A, y=n180^\circ+(-1)^nA$ where $n$ is any integer

As $\sqrt3-1=\tan60^\circ-\tan45^\circ=\dfrac{\sin(60-45)^\circ}{\cos60^\circ\cos45^\circ}=2\sqrt2\sin15^\circ$

Similarly, $\sqrt3+1=2\sqrt2\sin75^\circ=2\sqrt2\cos15^\circ$

$\endgroup$
  • $\begingroup$ @user307178, Please follow the last two lines $\endgroup$ – lab bhattacharjee Mar 20 '16 at 9:05
  • $\begingroup$ Thanks got it...My reputation is less so I can't upvote $\endgroup$ – user307178 Mar 20 '16 at 9:07
  • 1
    $\begingroup$ @user307178, I actually tried to derive the sine/cosine value of $$\dfrac{\sqrt3\pm1}{2\sqrt2}$$ without assuming them. $\endgroup$ – lab bhattacharjee Mar 20 '16 at 9:15
  • $\begingroup$ And I have learned a useful method to derive them! Because I always forget it. Thanks! $\endgroup$ – user307178 Mar 20 '16 at 9:25
  • $\begingroup$ Do you know a similar trick to get sin18°? That would be awesome $\endgroup$ – user307178 Mar 20 '16 at 9:29

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.